Gambaran Tingkat Pengetahuan Masyarakat tentang DAGUSIBU Obat di Lingkup Lansia Nagari Aur Begalung - Wahyuni, Fitri; Rasyadi, Yahdian; Ningsih, Wida; Elvionita, Cindy; Pharmaheri, Anugrah Putra (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2026)
In older adults, there is a decline in the ability to adapt to the external environment, accompanied by decreased physiological, cognitive, and psychological functions. These conditions may lead to errors in medication management and use among the elderly. One effort to prevent such problems is the correct implementation of the DAGUSIBU concept (Obtain, Use, Store, and Dispose of medicines). However, the level of knowledge of elderly people regarding DAGUSIBU has not been clearly identified, particularly in Nagari Aur Begalung, Pesisir Selatan Regency. This study aimed to describe the level of knowledge of the elderly community regarding DAGUSIBU medicines in Nagari Aur Begalung. This research employed an observational design with a cross-sectional approach. Data were collected using a structured questionnaire distributed to elderly respondents. The results showed that the majority of elderly respondents had a moderate level of knowledge regarding DAGUSIBU medicines, indicating that their understanding of proper medication management is not yet optimal. Therefore, continuous educational efforts are needed to improve elderly knowledge to ensure appropriate, safe, and rational use of medicines.